Students' mathematical argumentation ability in determining arguments or not arguments. (October 2019) - Indrawatiningsih, N; Purwanto; As'ari, A R; Sa'dijah, C; Dwiyana
Abstract: Someone who has critical thinking ability can use the exact criteria to evaluate an argument. This engages critical thinking to determine whether a claim or an argument which has been given is correct or not and whether the sentence which has been given is included an argument or not. To determine it, there must be clear evidence and logic explanation. The aim of this study is to investigate the argument in critical thinking ability. The students are asked to determine whether the information which has been given by the researcher is included an argument or not and give the reason. The information that is given by the researcher is in the form of triangle congruent evidence. The subject is the students in mathematics education who consist two people with criteria moderate (female student) and high academic ability (male student). This study is descriptive qualitative research. This result study was the student who had high academic ability was still not able to analyze more detail about an argument so he was called he did not have critical thinking ability. While the student who had moderate academic ability had been able to analyze that the information which was given was included an argument or not and was able to justify it so it could be concluded that she had critical thinking ability. It could decipherable that the student who had high academic ability was not sure understood about an argument.